MiR‐26a suppresses autophagy in swine Sertoli cells by targeting ULK2. (14th May 2018) - Ran, M; Li, Z; Cao, R; Weng, B; Peng, F; He, C; Chen, B
Contents: A large number of microRNAs (miRNAs) have been detected from porcine testicular tissues thanks to the development of high‐throughput sequencing technology. However, the regulatory roles of most identified miRNAs in swine testicular development or spermatogenesis are poorly understood. In our previous study, ULK2 (uncoordinated‐51‐like kinase 2) was predicted as a target gene of miR‐26a. In this study, we aimed to investigate the role of miR‐26a in swine Sertoli cell autophagy. The relative expression of miR‐26a and ULK2 levels has a significant negative correlation ( R 2 = .5964, p ≤ .01) in nine developmental stages of swine testicular tissue. Dual‐luciferase reporter assay results show that miR‐26a directly targets the 3′UTR of the ULK2 gene (position 618–624). In addition, both the mRNA and protein expression of ULK2 were downregulated by miR‐26a in swine Sertoli cells. These results indicate that miR‐26a targets the ULK2 gene and downregulates its expression in swine Sertoli cells. Based on the expression of marker genes (LC3, p62 and Beclin‐1), overexpression of miR‐26a or knock‐down of ULK2 inhibits swine Sertoli cell autophagy. Taken together, these findings demonstrate that miR‐26a suppresses autophagy in swine Sertoli cells by targeting ULK2 .